Nutritional insights into pulmonary fibrosis: a comprehensive review on the impact of vitamins - Qu, Yaqian; Zhao, Youliang (Frontiers in Nutrition, 2025)
Pulmonary fibrosis is a fatal interstitial disease characterized by diffuse alveolitis, abnormal fibroblast proliferation, and extracellular matrix (ECM) accumulation, resulting in structural lung destruction and impaired lung function. Numerous studies have demonstrated that vitamins appear to play a crucial role in regulating inflammatory responses, cell differentiation, redox homeostasis, and collagen synthesis. Beyond their conventional nutritional functions, specific vitamins have recently been found to modulate various biological processes involved in pulmonary fibrosis. This study aims to provide a comprehensive overview of the current understanding regarding the impact of vitamins on pulmonary fibrotic disease.